Damping Analyses of Structural Vibrations and Shunted Piezoelectric Transducers. (19th December 2011) - Mohammadi, Saber; Khodayari, Akram
Abstract : Piezoelectric transducers in conjunction with appropriate electric networks can be used as a mechanical energy dissipation device. Alternatively, undesired mechanical energy of a structure could be converted into electrical energy that can be dissipated through a shunt network in the form of Joule heating. This paper presents an experimental method to calculate damping energy in mechanical systems. However, the mathematical description of damping mechanism is much more complicated, and any process responsible for the occurrence of damping is very intricate. Structural and piezoelectric damping are calculated and analysed in the case of pulse switching or SSDI semiactive vibration control technique. This technique which was developed in the field of piezoelectric damping consists in triggering the inverting switch on each extremum of the piezoelectric voltage which induces an increase of the electromechanical energy conversion.